Ice Breaking Creating Fun Learning Perspectives on Learning Psychology and Neuroscience at MI Muhammadiyah 1 Ponorogo: Ice Breaking Menciptakan Pembelajaran Menyenangkan Perpsketif Psikologi Belajar dan Neurosains di Mi Muhammadiyah 1 Ponorogo - Katni; Rois, Adib Khusnul; R, Vivanda Ariani; Arifin, Ja’far (Universitas Muhammadiyah Sidoarjo, 2022)
This article discusses ice breaking in creating a fun learning perspective on neuroscience and learning psychology. This research is a field research on empirical experiences at the basic education level. The habit of using ice breaking at MI Muhamadiyah 1 Ponorogo has been going on for a long time, it has been held in all classes and at all levels, the results have a significant impact on improving the learning process and results. This article explains the various types of ice breaking that are used, that from a neuroscience perspective, ice breaking makes students' brains fresh, so that the brain will concentrate and will easily absorb information in the learning process. While in the perspective of learning psychology, ice breaking in the learning process will make students not feel bored in learning, can increase learning motivation and make students active and creative in the learning process. A conducive and pleasant climate makes everything that students learn easier and more fun for students.